A survey of fissure sealants and dental caries prevalence in the first permanent molars among primary school girls in Riyadh, Saudi Arabia - Alwayli, Hessa M.; Alshiha, Sattam A.; Alfraih, Yazeed K.; Hattan, Mohammed A.; Alamri, Abdullah A.; Aldossary, Mohammed S. (European Journal of Dentistry, 2017)
Objectives: To investigate the prevalence of caries and fissure sealants on the first permanent molars (FPMs) among 6–9-year-old girls in Riyadh, Saudi Arabia. Materials and Methods: The FPMs of 17,891 school girls from 120 randomly selected public primary schools were evaluated by visual and tactile examination for the carious status and the presence of fissure sealants. Chi-square test was used to analyze the data at level of 5%. Results: A total of 58,140 FPMs were assessed in the 17,891 children. Nearly 64.6% of the children were caries free. Only 1.3% of the children had at least one fissure sealant applied. At tooth level, the decayed FPMs counted for 24.6%. There was obvious underutilization of fissure sealants on the FPMs; 0.8% (n = 478). The caries prevalence in the mandibular FPMs (33%) was significantly higher than in the maxillary FPMs, 18.2% (P < 0.01). The proportion of carious FPMs increased with age of the children significantly (P < 0.01). There was no significant difference in the proportion of the presence of fissure sealants among the three different grade/age groups (P > 0.05). Conclusions: Caries prevalence in the FPMs was high and serious among this cohort of young students. This was contrasting the very low prevalence of fissure sealants.
Keywords: Dental caries; first permanent molar; fissure sealants; preventive dentistry